Rational design of a water-soluble NIR AIEgen, and its application in ultrafast wash-free cellular imaging and photodynamic cancer cell ablation. Issue 15 (21st March 2018) - Wang, Dong; Su, Huifang; Kwok, Ryan T. K.; Hu, Xianglong; Zou, Hang; Luo, Qianxin; Lee, Michelle M. S.; Xu, Wenhan; Lam, Jacky W. Y.; Tang, Ben Zhong
Abstract : The first water-soluble NIR AIEgen was synthesized and used for ultrafast wash-free cellular imaging and photodynamic cancer cell ablation. Abstract : The synthesis of water-soluble near-infrared (NIR)-emissive fluorescent molecules with aggregation-induced emission (AIE) characteristics and theranostic functions is highly desirable but remains challenging. In this work, we designed and readily prepared for the first time such a molecule with AIE features, good water-solubility and intense emission in the NIR region. This AIE luminogen (AIEgen) is able to specifically "light up" the cell membrane without the involvement of a washing procedure. Interestingly, the staining process can be performed by simply shaking the culture with cells at room temperature for only a few seconds after the addition of the AIEgen, indicating an ultrafast and easy-to-operate staining protocol. This is the first fluorescent "light-up" probe for cell-imaging that allows the combination of a short staining period (at the second-level) with a wash-free process. Additionally, the presented AIEgen has also been developed to serve as an excellent phototherapeutic agent for high efficiency generation of reactive oxygen species (ROS) upon visible light irradiation, which allows its effective application in the photodynamic ablation of cancer cells, demonstrating its dual role as an imaging and phototherapeutic agent.